2003
DOI: 10.1038/sj.hdy.6800301
|View full text |Cite
|
Sign up to set email alerts
|

Shell shape of the land snail Cornu aspersum in North Africa: unexpected evidence of a phylogeographical splitting

Abstract: Anatomical and molecular characters used to differentiate populations of the land snail Cornu aspersum (Helix aspersa) exhibit, in the western Mediterranean, definite and concordant patterns of correlation with geography. Scenarios involving Pliocene geological changes and postglacial expansion during the Pleistocene were proposed in previous studies to account for the establishment of this geographical structure. In the present work, we have performed a spatial analysis of variation in shell morphometrics, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 50 publications
5
32
0
2
Order By: Relevance
“…Flatter shells facilitate movement on substrates with foliated structures (e.g., leaf litter), whereas higher shells are more advantageous on substrate with a fine particle structure (e.g., soil) [48]. Several studies demonstrated that this feature is primarily genetically determined, but, within a given form, it may also be influenced by phenotype [49]. Therefore, the sampled snails have originated from habitats with different substrates or they belong to different subspecies.…”
Section: Resultsmentioning
confidence: 99%
“…Flatter shells facilitate movement on substrates with foliated structures (e.g., leaf litter), whereas higher shells are more advantageous on substrate with a fine particle structure (e.g., soil) [48]. Several studies demonstrated that this feature is primarily genetically determined, but, within a given form, it may also be influenced by phenotype [49]. Therefore, the sampled snails have originated from habitats with different substrates or they belong to different subspecies.…”
Section: Resultsmentioning
confidence: 99%
“…This land snail exhibits a great shell variation across geographical regions [43] and is characterized by physiological and morphological adaptations (e.g., metabolic depression, reduction of water-loss rate, thicker shell, reduced shell aperture, thicker epiphragm and supercooling ability) that enable it to inhabit dryer, colder and/or hotter environments by increasing the amount of time the snail can remain inactive [44][46]. Additionally, empirical evidence suggests that C. aspersum snails are energetically constrained by the mode of locomotion [47] and the cost of shell production during ontogeny [48].…”
Section: Methodsmentioning
confidence: 99%
“…To characterize shell size, we conducted a principal components analysis of log10-transformed linear shell measurements. To characterize shell shape, we performed a covariance PCA [35], which finds shape components that are separate from size. Covariance PCA analysis was conducted in ADE-4 [36], and PCA shape scores were obtained by an R program subroutine provided by A. Bellido.…”
Section: Methodsmentioning
confidence: 99%